The Influence of Parent’s Perception and Involvement in Purchasing Decision of Toys For Children - Ulfa, Milatul; Djamaludin, Moh Djemjem (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
Toys are